Genome sequencing in congenital cataracts improves diagnostic yield. Issue 9 (15th June 2021) - Ma, Alan; Grigg, John R.; Flaherty, Maree; Smith, James; Minoche, Andre E.; Cowley, Mark J.; Nash, Benjamin M.; Ho, Gladys; Gayagay, Thet; Lai, Tiffany; Farnsworth, Elizabeth; Hackett, Emma L.; et al.
Abstract: Congenital cataracts are one of the major causes of childhood‐onset blindness around the world. Genetic diagnosis provides benefits through avoidance of unnecessary tests, surveillance of extraocular features, and genetic family information. In this study, we demonstrate the value of genome sequencing in improving diagnostic yield in congenital cataract patients and families. We applied genome sequencing to investigate 20 probands with congenital cataracts. We examined the added value of genome sequencing across a total cohort of 52 probands, including 14 unable to be diagnosed using previous microarray and exome or panel‐based approaches. Although exome or genome sequencing would have detected the variants in 35/52 (67%) of the cases, specific advantages of genome sequencing led to additional diagnoses in 10% (5/52) of the overall cohort, and we achieved an overall diagnostic rate of 77% (40/52). Specific benefits of genome sequencing were due to detection of small copy number variants (2), indels in repetitive regions (2) or single‐nucleotide variants (SNVs) in GC‐rich regions (1), not detectable on the previous microarray, exome sequencing, or panel‐based approaches. In other cases, SNVs were identified in cataract disease genes, including those newly identified since our previous study. This study highlights the additional yield of genome sequencing in congenital cataracts. Abstract : Genome sequencing in congenital cataracts has a 77% yield, 10% higher than exome sequencing.